Design, modelling and simulation of a remotely operated vehicle – Part 2 - Le, Khoa Duy; Nguyen, Hung Duc; Ranmuthugala, Dev (Journal of Computer Science and Cybernetics, 2014)
Continuing the previously published study [4], this paper focuses on hardware and Virtual Reality (VR) model development of a three-thruster Remotely Operated Vehicle (ROV). The paper included setting up an on-board electronic system with the associated suite of sensors and the required communication protocol. This system utilizes a master-slave structure, which consists of an onshore station computer and an on-board open source microcontroller. To improve the controllability of the driving system, a VR model of the ROV is designed to reflect the altitude and attitude of the physical vehicle. By using the feedback signals from the sensors, the VR model operates in a similar manner to the actual vehicle. Hence, it provides the operator with the capability to monitor the ROV operation within a virtual environment and enables the operator to control the ROV based on the visual inputs and feedback. Finally, real time simulations are presented to validate the interaction between the ROV operator and the VR model. To provide realistic operational conditions, the effects of sensor noise and water current disturbances are included in the simulation program. The results show that the performance of the VR ROV is stable even with these disturbances.